Literatur review: pengaruh latar belakang sosial ekonomi orang tua terhadap prestasi belajar siswa di sekolah dasar - Yesi Anita Sari; Zulfatu Zainiyah; Mohammad Edy Nurtamam (Jurnal Pendidikan Dasar, 2025)
This study reviews research on the influence of parents' socioeconomic background on student learning achievement using the systematic literature review (SLR) method. The population includes all articles discussing this topic, published in indexed journals between 2015 and 2025. Articles were selected using the keywords "Socio-Economic" and "Learning Achievement" through Publish or Perish software. From 100 articles, 16 were chosen based on inclusion and exclusion criteria for further analysis. Data collection involved gathering literature from journals in the Google Scholar database. This review highlights how parents' socioeconomic background impacts students' learning achievement in elementary school, not only through the ability to provide learning facilities but also by influencing motivation, parental attention, and the quality of the educational environment. The findings can guide policymakers and educators in designing effective interventions, such as improving teaching quality, providing learning facilities, and encouraging comprehensive parental involvement. A holistic approach that considers economic, social, and psychological aspects can improve student learning outcomes and reduce educational gaps.